Strategi Misi Kristus dan Perkembangannya di Masa Jemaat Mula-Mula serta Implikasinya untuk Gereja Lutheran Indonesia - Fenius Gulo (Sekolah Tinggi Theologia Nazarene Indonesia, 2023)
The mission of Lutheran churches in Indonesia has recently been considered less developed than other streams, such as Charismatics and Pentecostals. This is due to the lack of significance in carrying out mission strategies by the Lord Jesus. It can be believed that the success of the mission of the Lord Jesus was influenced by the strategy used in carrying out the mission itself. In this study, researchers used a qualitative research method emphasizing literature study. Therefore, the Bible is the main source in this study, while books and journals are used as references. After conducting a study based on qualitative research methods, the focus of this research is proven that Jesus' mission strategy has contributed to significantly impact the success and development of the mission. The strategies of the Lord Jesus in carrying out His mission are choosing a team to be discipled, teaching in various places, the existence of mission material, serving with supernatural power, serving holistically, and not looking at people from various statuses. Jesus was very focused on fostering disciples to become evangelists and church planters. The strategy of the Lord Jesus, as described in this study, is very appropriate when applied in Lutheran churches in Indonesia so that this church stream will be more advanced in mission in the future.